Electron Sublayers and the Associated Magnetic Topologies in the Inner Low‐Latitude Boundary Layer. Issue 11 (13th June 2019) - Dong, X.‐C.; Dunlop, M. W.; Trattner, K. J.; Wang, T.‐Y.; Pu, Z. Y.; Zhao, J.‐S.; Cao, J.‐B.; Giles, Barbara; Russell, C. T.
Abstract: The low‐latitude boundary layer (LLBL) plays an important role as a transition layer in coupling the magnetosheath and magnetosphere. Using high‐resolution Magnetospheric Multiscale data, we analyze the electron distributions in the inner region of the LLBL, during an active period of magnetic reconnection under southward interplanetary magnetic field. According to the measured electron energy anisotropy, we suggest that this inner LLBL can be divided into six sublayers corresponding to three types of magnetic field‐line topologies: (1) open magnetic field line topology from magnetosheath to southern magnetosphere, (2) open magnetic field line topology from magnetosheath to northern magnetosphere, and (3) reclosed magnetic field line topology. These different scenarios indicate that magnetic reconnection occurs at both northern and southern locations of the spacecraft and thus suggest that magnetic reconnection was active simultaneously at high and low latitude on the magnetopause, equatorward of the cusps. These results provide evidence within the LLBL for such multiple X‐line formation. Plain Language Summary: Magnetic reconnection is a fundamental energy conversion process in space, astrophysical, and laboratorial plasmas. At the Earth's magnetopause, the occurrence and location of magnetic reconnection are of particular interest. By analyzing the detailed sublayers of the inner low‐latitude boundary layer, we identified different magnetic field‐line topologies. The different field line topologies indicate that magnetic reconnection happens both north and south of the spacecraft and thus suggest that magnetic reconnection was active at both the high‐ and low‐latitude dayside magnetopause. These results provide further evidence for large‐scale multiple X‐line formation. Key Points: Observational results show that the inner LLBL contains multiple electron sublayers, which are more complex than previous results These sublayers include three different magnetic field line topologies The study reports evidence in the LLBL that high‐ and low‐latitude magnetic reconnection can happen simultaneously under southward IMF